Solid-state host–guest influences on a BODIPY dye hosted within a crystalline sponge. (10th August 2020) - Gee, William J.; Shepherd, Helena J.; Dawson, Daniel M.; Ashbrook, Sharon E.; Raithby, Paul R.; Burrows, Andrew D.
Abstract : Hosting a BODIPY dye in a crystalline sponge bathochromically shifts luminescent emission. Abstract : Manipulating the emission characteristics of phosphors is a viable strategy to produce unique, and thus difficult to replicate, security optical features that are useful in anticounterfeiting applications. Here, a fluorophore, BODIPY 493/503, displayed altered solid-state emission characteristics upon being hosted within a crystalline molecular flask. Specifically, a bathochromic shift of 939 cm −1 was observed ( λ (max) : 633 → 673 nm), with a concomitant reduction in emission intensity, and emission dependency on excitation wavelength. Multiple factors likely contribute to this behaviour, such as emission filtering by the host framework, exciplex formation between BODIPY and the electron-deficient framework, and collisional quenching between the host and guest. Here we prioritize solid-state analyses to explore these factors, including electron density mapping of the framework pores, and multinuclear solid-state NMR spectroscopy.